2021
DOI: 10.1111/jog.14902
|View full text |Cite
|
Sign up to set email alerts
|

Malignant struma ovarii: From case to analysis

Abstract: Aim: To evaluate the clinico-pathologic features, treatment options, prognostic factors, and survival outcomes of malignant struma ovarii based on a systematic literature review in association with our case study. Methods: A systematic review of the medical literature was performed to identify articles about malignant struma ovarii from January 1983 until July 2020. We evaluated 178 cases. Results: The 5-year progression-free survival (PFS) and overall survival (OS) of the entire cohort was 72.5% and 91%, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 133 publications
1
13
0
2
Order By: Relevance
“…Several large cohort studies showed similar OS outcomes in patients with MSO, regardless of the presence of metastatic lesions at initial diagnosis ( 9 12 ). In 2015, a study of 68 patients with MSO showed an OS rate of 96.7, 94.3, and 84.9% in 5, 10, and 20 years, respectively ( 9 ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Several large cohort studies showed similar OS outcomes in patients with MSO, regardless of the presence of metastatic lesions at initial diagnosis ( 9 12 ). In 2015, a study of 68 patients with MSO showed an OS rate of 96.7, 94.3, and 84.9% in 5, 10, and 20 years, respectively ( 9 ).…”
Section: Discussionmentioning
confidence: 94%
“…In patients ( n = 125) with MSO confined to the ovary, the OS rate was 91.5, 85.2, and 85.2% in 5, 10, and 20 years, respectively. Another systemic review showed the 5-year progress-free survival to be 72.5% ( 12 ). Our study had the largest patient cohort and confirmed the excellent prognosis of MSO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease is mostly benign and unilateral, and malignant transformation and metastasis are extremely rare. The malignant transformation rate is as low as 5%, and the most common malignancies are papillary carcinoma (approximately 70%) and follicular carcinoma (approximately 30%)[ 4 , 6 , 10 - 11 ]. MSO metastasizes in approximately 5%-23% of cases[ 2 , 10 ], mainly leading to lymphatic and blood metastasis and peritoneal and omental metastasis, but metastases have also been seen in the pelvis, liver, lung, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with both MSO and thyroid cancer are generally classified into three conditions: (1) Metastasis of thyroid cancer to the ovary; (2) Metastasis of MSO to the thyroid; and (3) Concurrent occurrence of thyroid cancer and MSO[ 11 ]. This patient had a solid cystic mass with mixed echogenicity measuring approximately 0.6 cm x 0.5 cm x 0.3 cm in size on an ultrasound examination of the left lobe of the thyroid gland.…”
Section: Discussionmentioning
confidence: 99%